Numerical modeling of local pharmacokinetics associated with drug-eluting stent - Jahid Ferdous (2009)
Atherosclerotic plaque formation in the arterial wall is the major cause of stenotic coronary disease. To restore distal blood supply and overcome restenosis presented by bare-metal stents, drug-eluting stent (DES) implantation is widely used. However, the long-term efficacy of this mode of treatment is not well-established. A detailed study of the drug delivery system is expected to give a better insight about what is required to improve the design of DES to achieve its long-term effect. Physiological transport forces, biological tissue properties, drug physiochemical properties and stent design are believed to play important roles in drug release, its subsequent deposition and distribution in the arterial wall. Therefore, it is important to consider these factors when modeling drug delivery system. In this study, a 2-dimensional model where drug transfer was coupled with luminal and transmural flow was used to investigate post-stenting local pharmacokinetics in arterial wall. Moreover, drug interaction with binding sites was also considered and treated as a reversible binding process. Paclitaxel and heparin were used to examine the effect of drug nature on local pharmacokinetics. Using this model, the effects of blood velocity, inter-strut distance, strut shape, and strut length-to-height ratio on local pharmacokinetics were also investigated. Further, the single-layered arterial wall model was extended to multi-layered model to examine the impact of drug and tissue properties associated with different layers of the arterial wall. Finally, atherosclerotic plaque was incorporated in the model to study the effect of plaque‘s geometry and nature on local pharmacokinetics.